Magnetostriction of a single cubic laves phase compound Tb0.27Dy0.73Fe2 - T. Methasiri (2018)
The magnetostriction of a single crystal cubic Laves phase compound Tb 0.27 Dy 0.73 Fe 2 is measured with the applied field (0-25 kOe) in the [111] direction in the temperature range between 80 and 300 K. Evidence is seen of a possible transition to the[uv0] easy axis phase during the spin re-orientation form [100] easy axis direction to the [110] easy axis direction. © 1987.